2018
DOI: 10.17650/2222-8721-2018-8-2-25-32
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of electrophysiological activity of the cerebral cortex in children with arthrogryposis

Abstract: Контакты: Евгений Дмитриевич Благовещенский zhenja@gmail.comВведение. Артрогрипоз -один из наиболее тяжелых врожденных пороков развития опорно-двигательного аппарата, характеризующийся наличием 2 и более контрактур крупных суставов, поражением мышц, а также передних рогов спинного мозга. Одной из основных проблем, обусловливающих ограничение или невозможность самообслуживания пациентов, является отсутствие активных движений в суставах верхних конечностей, которое восстанавливается путем аутотрансплантации мышц… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, the neural synchronization of the patients was similarly observed in all of the categories of motor-related video scenes, suggesting that ISC is independent to the stimulus' motor-related content in this population. Therefore, the thesis that embodiment is rather general in its manifestations, rather than being limited to specific cognitive aspects closely related to an agent's sensorimotor capacities, is supported [38]. In addition, our findings agree with the idea of embodied simulation [14], and with the crucial role the human body plays in the constitution of how we understand the world of others [59].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the neural synchronization of the patients was similarly observed in all of the categories of motor-related video scenes, suggesting that ISC is independent to the stimulus' motor-related content in this population. Therefore, the thesis that embodiment is rather general in its manifestations, rather than being limited to specific cognitive aspects closely related to an agent's sensorimotor capacities, is supported [38]. In addition, our findings agree with the idea of embodied simulation [14], and with the crucial role the human body plays in the constitution of how we understand the world of others [59].…”
Section: Discussionsupporting
confidence: 85%
“…For example, Koriakina et al [37] revealed that the auditory and visual memory in AMC and OBPL patients are not developed in the same way as in healthy children. Blagoveshchensky et al [38] suggest a possible dysfunction in AMC children at a cognitive level as well, as reflected in the altered pattern of their resting state brain activity. Hence, one can tentatively hypothesize that the differences between patients and healthy controls in terms of perceptual-cognitive processes may well not be limited to the processing of motor actions, but they might be more widely and robustly embodied in nature.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that some muscles have smaller cortical representation, and accordingly, less cortical voluntary control. Also we showed recently that there is a change in the basic EEG rhythms in children with arthrogryposis (Blagoveschenskiy et al, 2018), which can also be a reflection of the plastic changes in the motor cortex. Perhaps functional mapping of the cortical representations of the possible donor's muscles may give a better answer to the question–which of the donor muscles is most suitable for such an operation.…”
Section: Which Muscle Is the Most Suitable For The Autotransplantation?mentioning
confidence: 74%
“…The involvement of modern neurotechnology may facilitate an understanding of the psychophysiological changes that occur in the brain in children with motor disorders [39]. It has been shown that, in such children, there is a significant decrease in the power of the main EEG rhythms [40]; moreover, specific rearrangements in the brain that are associated with a change in the functional representation of certain muscles of the upper extremities have been found in children with AMC [41]. It is likely that similar changes should occur in children diagnosed with OBPP, but there is no exact data on this issue.…”
Section: Discussionmentioning
confidence: 99%